Analisis Kesesuian Penyusunan RPP Tematik pada Prodi Pendidikan Guru Madrasah Ibtidaiyah IAIN Manado - Maulana Mohammad Fahmiy (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The problem in this study is that there are still many prospective teacher students who still have difficulty making lesson plans. Especially in the Microteching course which takes place in semester VI. This study aims to identify the students' understanding of the Madrasah Ibtidaiyah Teacher Education Program at IAIN Manado in preparing lesson plans (RPP). The research method applied is qualitative research with a descriptive type. Data collection techniques in this study were observation and documentation techniques. Data analysis used descriptive analysis by reviewing several lesson plans made by students. Based on the results of data analysis, it can be concluded that the understanding of prospective teacher students is still not good, there is still a wrong understanding regarding the preparation of lesson plans (RPP). Understanding related to compiling Basic Competencies that are still not quite right, without regard to Core Competencies. RPP is a decrease from the syllabus that students must pay attention to in preparing it.